Bioethics on the Congressional Agenda - Capron, Alexander Morgan (The Hastings Center report, 1989)
Since their initial authorization by Congress in 1985, the Bio-medical Ethics Board and its advisory body, the Biomedical Ethics Advisory Committee, have led a precarious and often politically troubled existence. Today, they are poised to take up their mandate to examine “the ethical, social, and legal implications of advances in biomedical research and technology.”